La morale chrétienne de Schleiermacher: Présentation et perspectives pour une étique théologique - Gaziaux, Éric (Revue théologique de Louvain, 2024)
The purpose of this article is to present Schleiemarcher’s conception of Christian morality. Ethics, both philosophical and Christian, were a constant preoccupation of his thinking. In order to present it, this contribution first recalls Schleiermacher’s organisational structure of knowledge, then considers philosophical ethics within this system, and thirdly situates the place of theology. In the fourth stage, the relationship and differences between Schleiermacher’s 'doctrine of faith' and his christian morality are outlined, before presenting the relationship between philosophical ethics and Christian moral doctrine. The sixth section describes the method and structure adopted by Schleiermacher’s Christliche Sitte, which is little known in French-speaking circles. The final section identifies the fundamental lines of thought, in the light of this philosopher, on the relationship between Christian morality and philosophical ethics, as well as its links with fundamental statements of christian faith.